Optimized Synthesis and Calcination of Nickel Phosphate: Structural and Thermal Characterization - Faradis, Royyan; Lumban Gaol, Binaria; Jovita, Stella; Fitri Ulfindrayani, Ika; Kris Murwani, Irmina (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2025)
Nickel Phosphate (NiP) has been successfully synthesized through the precipitation method. The effect of pH, stirring temperature, and Ni:P molar ratio on NiP formation has been studied. The optimization showed that NiP is formed at pH 6, stirring temperature of 90 °C, and a molar ratio of Ni:P of 3:6. Then, the obtained powder was calcined at a temperature of 350-800 °C. The synthesised NiP was characterized using X-ray powder diffraction (XRD), Fourier Transform Infrared (FTIR) spectroscopy, nitrogen adsorption-desorption, and Scanning Electron Microscopy (SEM). The characterization results showed that the NiP structure was amorphous at 350-600 °C and transformed into a monoclinic crystalline of Ni₃(PO₄)₂ at 800 °C. Nitrogen adsorption isotherms showed that the NiP result had a predominance of micropores with little mesoporous contribution. Sample NiP_350 shows the highest surface area (9.94 m2/g) with a more uniform pore distribution. FTIR-pyridine analysis identified the existence of both Lewis and Brønsted acid sites, with the predominance of Brønsted acid at low calcination temperatures. The increase in calcination temperature resulted in reduced surface area and total acidity due to pore coalescence and dehydration, which was in line with the results of SEM, which showed a denser morphology. Overall, these results confirm that variations in synthesis and calcination conditions play an important role in determining the textural properties, acidity, and structure of NiP, which makes them potential candidates for catalysis and adsorption applications.